Factor accumulation and total factor productivity growth: ASEAN economies - Subramaniam Munusamy,; Yogambigai Rajamoorthy, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the contribution of factor accumulation on Total Factor Productivity (TFP) growth in the eight ASEAN countries with specific reference to short-term and long-term estimation effect. Using Mean Group (MG) estimator on data between 1990 and 2018, this study found a significant relationship between capital accumulation and TFP growth. Our analysis suggests that the positive growth on TFP in most ASEAN countries was due to the short-run effect of capital accumulation. This study also found that the ASEAN economies have a relatively lower rate of capital utilization that adversely affects TFP growth in the long run. The contribution of TFP to output growth is paramount for the sustainability of long-term economic growth. Thus, ASEAN countries need to accelerate capital accumulation and technology adoption in the short-term and utilize idle capital in the long-term.